Early identification and brief intervention for risky drinkers in Finnish occupational health services - Kuokkanen, Matti; Heljälä, Leena (SJWEH Supplements, 2005)
' ' OBJECTIVES ': 'Hazardous drinking is a problem in many occupational settings. Finland has been active in implementing early identification and brief intervention with respect to risky drinking habits. To obtain information on these activities in Finnish occupational health services, a questionnaire survey was carried out as part of a national survey of occupational health services in 1997 and 2000. ' ' METHODS ': 'In 1998 and 2001, a questionnaire was sent to all Finnish occupational health centers in operation in 1997 and 2000, respectively. Information was obtained on 770 centers in 1998 (83.1%) and 672 centers in 2001 (77.6%). Every center filled out one questionnaire. The outcome variable was activity involving early identification and brief intervention for risky drinking in 1997 and in 2000, respectively. Statistical differences were tested with the chi-square test. ' ' RESULTS ': 'Early identification and brief intervention for risky drinking increased the most in eastern Finland from 1997 to 2000 (from 30% to 55%). Large centers increased their early identification and brief intervention (from 48% to 69%) more than the small ones (from 20% to 30%) did. ' ' CONCLUSIONS ': 'There was a clear increase in early identification and brief intervention for risky drinking over a period of 3 years, but the number of clients receiving such a service from occupational health units is still low.
Keywords: brief intervention; drinker; early identification; Finland; hazardous drinking; identification; intervention; occupational health services; OHS; risky drinker